IMPROVING OF SOCIETY'S KNOWLEDGE ABOUT PREVENTION OF CORONARY HEART DISEASE FROM AN EARLY AGE - Meli Diana; Dini Prastyo Wijayanti; Dimas Hadi Prayoga; Nurhanifah Mawarni; Kiki Widyasari (Community Service Journal of Indonesia, 2021)
Community Service activities organized by Health Polytechnic of Kerta Cendekia, Sidoarjo in collaboration with Baitul Mal Hidayatulloh (BMH) Sidoarjo held a Health Talk Show which was broadcast live streaming on the POS DAI SIDOARJO channel with the theme "Prevention of Coronary Heart Disease Early". The Health Talk Show was held on Sunday, April 11, 2021 at the BMH office in Pondok Mutiara Sidoarjo. This activity was carried out in a team consisting of three lecturers of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2 students, and a team from BMH Sidoarjo. The activity was arranged by the team for two weeks, starting from determining the theme of the activity, the form of the activity, the timing of the activity, and the socialization of the activity through social media. This activity was witnessed by the wider community, especially in the Sidoarjo area. As a form of evaluation, this community service activity ran smoothly, seen 250 viewers on the YouTube channel, viewers were enthusiastic about participating in the activity by asking questions via live chat.